Identifying students’ challenges and strategies to produce English-speaking utterances - Qonita, Qonita; Saraswati, Girindra Putri Dewi (Universitas Negeri Semarang, 2025)
Previous research has examined English-speaking challenges, but rarely has it linked them to specific strategies based on Oxford’s (1990) Strategy Inventory for Language Learning (SILL). This study addresses that gap by identifying students’ challenges and strategies to produce English-speaking utterances, especially among English education students in Universitas Negeri Semarang, where speaking is still a common yet underdeveloped skill. The researcher employed qualitative research, and the participants of this study were 22 students in the sixth semester of the English education study program at Universitas Negeri Semarang. The data were gathered through questionnaires and interviews, then analyzed using qualitative methods. The findings revealed that although over 80% of the students reported frequently using English in interaction on campus, many still encountered significant challenges. The most prevalent challenges faced by students in speaking include anxiety, fear of making mistakes, lack of confidence, lack of vocabulary, and lack of grammar, which significantly affected students’ fluency and accuracy. The finding shows that, memory, cognitive, and compensation strategies were commonly used to address vocabulary and lack of grammar. Metacognitive and affective strategies helped manage anxiety and hesitation, while social strategies supported speaking development. The findings imply that promoting specific strategic awareness can improve speaking proficiency and confidence. Teachers are encouraged to integrate explicit strategy training into speaking instruction, create low-anxiety environments, and encourage collaborative learning. Future research should explore how individual learner differences affect the effectiveness of these strategies in various contexts and over longer periods of language learning.